Risk spillovers between global corporations and Latin American sovereigns: Global factors matter - José Eduardo Gómez González; Jorge Uribe; Oscar M. Valencia (Inter-American Development Bank (IDB), 2022)
This paper studies volatility spillovers in credit default swaps (CDS) between the corporate sectors and Latin American countries. Daily data from October 14, 2006, to August 23, 2021, are employed. Spillovers are computed both for the raw data and for filtered series which factor out the effect of global common factors on the various CDS series. Results indicate that most spillovers occur within groups-that is, within the series of sovereign CDS contracts and the price contracts of CDS issued by global corporations. However, considerable spillovers are also registered between LAC sovereigns and corporations. Interesting differences are encountered between filtered and unfiltered data. Specifically, spillovers from countries to corporations are overestimated (by about 4.3 percentage points) and spillovers from corporations to sovereigns are underestimated (by about 5.8 percentage points) when unfiltered data are used. This result calls for a revision of results obtained from studies that do not consider the role played by global common factors in system spillovers. Like in most related studies, spillovers show considerable time variation, being larger during times of financial or economic distress. When looking at total system spillovers over time, those corresponding to unfiltered series are always larger than those corresponding to filtered series. The difference between the two time series is largest in times of distress, indicating that global factors play a major role in times of crisis. Similar conclusions are derived from network analysis.
Keywords: G01; G12; C22; 330; corporate debt; factor models; filtered and unfiltered data; LatinAmerican countries; volatility spillovers